The DNA damage response induces antigen presenting cell‐like functions in fibroblasts. Issue 4 (16th February 2014) - Tang, Melissa Li Fang; Khan, Muznah Khatoo Nazar; Croxford, John Ludovic; Tan, Kar Wai; Angeli, Veronique; Gasser, Stephan
<x xml:space="preserve">Abstract</x> The DNA damage response (DDR) alerts the immune system to the danger posed by DNA damage through the induction of damage‐associated molecular pattern molecules, chemokines, and ligands for activating immune receptors such as lymphocyte function‐associated antigen 1 (LFA‐1), NKG2D, and DNAX accessory molecule 1 (DNAM‐1). Here we provide evidence that OVA257–264‐pulsed fibroblasts gain the ability to activate naïve OT‐I CD8+ T cells in response to DNA damage. The ability of fibroblasts to activate OT‐I CD8+ T cells depended on the upregulation of ICAM‐1 on fibroblasts and DNAM‐1 expression of CD8+ T cells. OVA257–264‐pulsed fibroblasts were able to induce a protective T‐cell response against B16‐OVA cells in a DDR‐dependent manner. Hence, the DDR may alert the immune system to the presence of potentially dangerous cells by upregulating the expression of ligands that can induce the activation of innate and adaptive immune cells.